Access, achievements, and aspirations: The impacts of school tracking on student outcomes - Maximilian Bach; Thilo Klein; Sarah McNamara (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Though the use of tracking policies to stratify students is commonplace, evi- dence concerning the effects of ability-based tracking on student performance is mixed. Using rich data from the Hungarian secondary school centralized assignment mechanism and a quasi-experimental framework, we find that at- tending the highest track noticeably improves standardized test scores and university aspirations two years post-match. Heterogeneity analysis finds this effect is independent of socioeconomic status, prior achievement, and parents' educational attainment, and we find only limited evidence of peer spillover effects in terms of academic ability. Given socioeconomic disparities in track placement, tracking may reinforce educational inequality.
Keywords: I21; I24; I28; E47; C26; 330; education; school choice; tracking; centralized school admissions; student achievement; inequality of opportunity